Influence of initial dissolved oxygen concentration on fenton's reagent degradation - Aris, A.; Sharratt, P. N. (Selper Ltd., 2006)
The effect of initial dissolved oxygen concentration (IDOC) on Fenton's reagent degradation of a dyestuff, Reactive Black 5 was explored in this study. The study was designed, conducted and analysed based on Central Composite Rotatable Design using a 3-1 lab-scale reactor. The participation of O2 in the process was experimentally observed and appears to be affected by the dosage of the reagents used in the study. The IDOC was found to have a significant influence on the process. Reducing the IDOC from 7.5 mg 1-1 to 2.5 mg 1-1 increased the removal of TOC by an average of about 10%. Reduction of IDOC from 10 mg 1-1 to 0 mg f' enhanced the TOC removal by about 30%. The negative influence of IDOC is likely to be caused by the competition between the O2 and the reagents for the organoradicals. A model describing the relationship between initial TOC removal, reagent dosage and IDOC has also been developed.